Limitations of COVID-19 Fever Clinic as the First Point of Contact: Are We Relying Too Much? An Experience from a Tertiary Center - Shrestha, Deepak (Journal of Lumbini Medical College, 2020)
In Nepal, after the first case was diagnosed with Corona Virus Disease -19 (COVID -19) in a 32-year-old returnee from Wuhan, China on 13 January 2020, it took more than four months to reach a figure of 500 infected cases. Seventy of them have already recovered and returned home. However, the curve has been taking a steeper slope after the first 50 cases were documented. With the first mortality from COVID-19 confirmed on 16th May, 2020, the fact that this pandemic is tightening its grip in the country is more evident now. And with each passing day, more cases are being diagnosed. In such a situation, strategies of screening the infected/suspects are of paramount importance and those already in place should be strengthened. On March 19, the Nepal Medical Council asked all hospitals, both private and public, with over 100 beds to operate a separate fever clinics and postpone elective surgeries to conserve resources for an outbreak. Such fever clinics aim at separating and filtering out the suspected/ diagnosed COVID-19 patients. Arguably started first in Kathmandu Medical College, fever clinics now have been established and run in almost every large health care centers. United Nations International Children’s Emergency Fund (UNICEF) has been pivotal in supporting some of these centers. Rising up to the task, Lumbini Medical College and Teaching Hospital started its fever clinic from 22 March 2020 in a separate makeshift place which later moved to a more organized structure. The fever clinic is set up in a separate area in order to keep off suspected patients from the main hospital.